Navigating Change Orders in Rail Construction - Mohd Afzan, Nur Aini Firzanah; Ismail, Mohamad Zahierruden (Journal of Construction in Developing Countries, 2026)
The construction industry is a vital sector driving economic growth and infrastructure development. However, it faces persistent challenges, particularly in large-scale projects like rail construction, where change orders frequently cause disruptions. In Malaysia, rail projects are critical for modernising transportation networks, but the complexity of managing change orders often leads to significant delays, cost overruns and administrative bottlenecks. This study aims to examine the challenges associated with change order management practices in Malaysian rail construction projects, with the broader intention of providing insights that can inform more effective project delivery. To achieve this aim, the specific objective of the research is to identify and analyse the key challenges in the practice of change order management processes within rail construction projects. A qualitative approach was adopted, involving semi-structured interviews with eight professionals from companies actively contributing to the rail industry, identified through the Malaysian Rail Supporting Industry Roadmap 2030 published by the Malaysia Industry-Government Group for High Technology. The study employed purposive and snowball sampling techniques, recognising the specialised nature of the rail construction community. The findings revealed a total of 15 raw challenges across the 3 phases of the change order management framework, which were subsequently consolidated into 9 overarching themes to capture the recurring issues in change order management implementation within rail projects. The study further underscores the potential of integrating lean construction principles, particularly planning and control practices, as targeted strategies to address these challenges. By providing insights into both the existing issues and opportunities for improvement, this study contributes to strengthening change order management practices and advancing the delivery of rail construction projects in Malaysia.